A genomic view of food-related and probiotic Enterococcus strains - Bonacina, Julieta (2017)
The study of enterococcal genomes has grown considerably in recent years. While special attentionis paid to comparative genomic analysis among clinical relevant isolates, in this study we performedan exhaustive comparative analysis of enterococcal genomes of food origin and/or with potential tobe used as probiotics. Beyond common genetic features, we especially aimed to identify those thatare specific to enterococcal strains isolated from a certain food-related source as well as features presentin a species-specific manner. Thus, the genome sequences of 25 Enterococcus strains, from 7different species, were examined and compared. Their phylogenetic relationship was reconstructedbased on orthologous proteins and whole genomes. Likewise, markers associated with a successfulcolonization (bacteriocin genes and genomic islands) and genome plasticity (phages and clusteredregularly interspaced short palindromic repeats) were investigated for lifestyle specific genetic features.At the same time, a search for antibiotic resistance genes was carried out, since they are of bigconcern in the food industry. Finally, it was possible to locate 1617 FIGfam families as a core proteomeuniversally present among the genera and to determine that most of the accessory genes codefor hypothetical proteins, providing reasonable hints to support their functional characterization.